Pendidikan Akhlak yang Terkandung dalam Buku “Yang Hilang dari Kita: Akhlak” Karya Muhammad Quraish Shihab - Khoiriyah, Khoiriyah; Ni’mah, Mamluatun; Herwati, Herwati (STAI Auliaurrasyidin Tembilahan, 2023)
This study aims to find out how moral education is according to the perspective of Muhammad Quraish Shihab in his book entitled